Integrasi University Social Responsibility (USR) Melalui Penguatan Pemahaman Green Accounting Pada Mahasiswa Akuntansi - Dhina Mustika Sari (AMMA : Jurnal Pengabdian Masyarakat, 2025)
University Social Responsibility (USR) is a form of social responsibility of higher education institutions in internalizing the value of sustainability through the implementation of the Tri Dharma (Three Pillars of Understanding), particularly in the learning aspect. One form of USR implementation is strengthening the understanding of green accounting that integrates environmental and social dimensions into accounting practices. This community service activity was carried out through a participatory approach at STIE Nusantara Sangatta, involving 47 students. This activity aims to improve students' understanding of green accounting and its relevance to social responsibility. Evaluation was carried out through a pre-test and post-test mechanism to measure the effectiveness of the activity. The evaluation results showed a significant increase in student understanding after the workshop, which was marked by a shift in scores from the categories of less understanding and not understanding to the categories of understanding and very understanding. This activity emphasizes the strategic role of higher education institutions through the USR framework in developing students with social and environmental awareness as a provision for making professional decisions oriented towards sustainability.